Prenatal exposure to binge pattern of alcohol consumption: mental health and learning outcomes at age 11. - Sayal, Kapil; Heron, Jon; Draper, Elizabeth; Alati, Rosa; Lewis, Sarah; Fraser, Robert; Barrow, Margaret; Golding, Jean; Emond, Alan; Davey Smith, George; Gray, Ron (European Child & Adolescent Psychiatry, 2014)
The objective of the study is to investigate whether episodic binge pattern of alcohol consumption during pregnancy is independently associated with child mental health and academic outcomes. Using data from the prospective, population-based Avon Longitudinal Study of Parents and Children (ALSPAC), we investigated the associations between binge patterns of alcohol consumption during pregnancy (≥4 drinks per day) and child mental health [as rated by both parent ( n = 4,610) and teacher ( n = 4,274)] and academic outcomes [based on examination results ( n = 6,939)] at age 11 years. After adjusting for prenatal and postnatal risk factors, binge pattern of alcohol consumption (≥4 drinks in a day on at least one occasion) during pregnancy was associated with higher levels of mental health problems (especially hyperactivity/inattention) in girls at age 11 years, according to parental report. After disentangling binge-pattern and daily drinking, binge-pattern drinking was independently associated with teacher-rated hyperactivity/inattention and lower academic scores in both genders. Episodic drinking involving ≥4 drinks per day during pregnancy may increase risk for child mental health problems and lower academic attainment even if daily average levels of alcohol consumption are low. Episodic binge pattern of drinking appears to be a risk factor for these outcomes, especially hyperactivity and inattention problems, in the absence of daily drinking.